Hubungan Antara Penggunaan Gadget dengan Interaksi Sosial pada Siswa Madrasah Tsanawiyah Negeri 3 Demak Kelas VII - Dian Fakhrul Muiz; Wahyu Endang Setyowati; Betie Febriana (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Social interaction is a reciprocal relationship that occurs between individuals and groups. In the digital era, gadget use has become an inseparable part of students’ daily activities. Excessive gadget use may negatively affect students’ social behavior, especially their ability to communicate and interact with peers. If left unmanaged, students may become more focused on their gadgets rather than their surrounding environment. This research employed an analytic correlation design with a cross-sectional approach. A total of 158 respondents were selected using a random sampling technique. Data were collected through a gadget-use questionnaire (20 items) and a social-interaction questionnaire (10 items). Data were analyzed using the Chi-Square statistical test. The majority of students were categorized as having mild gadget dependency. Most respondents showed good social interaction. The Chi-Square analysis revealed a p-value of 0.0001 (p < 0.05), indicating a significant relationship between gadget use and social interaction among seventh-grade students at MTsN 3 Demak. There is a significant relationship between gadget use and social interaction. Higher levels of gadget use tend to be associated with lower levels of social interaction.